Intersecting household-level health and socio-economic vulnerabilities and the COVID-19 crisis: An analysis from the UK - Júlia Mikolai; Katherine Keenan; Hill Kulu (Elsevier, 2020)
The effects of COVID-19 are likely to be socially stratified. Disease control measures introduced during the COVID-19 pandemic mean that people spend much more time in their immediate households, due to lockdowns, the need to self-isolate, and school and workplace closures. This has elevated the importance of certain household-level characteristics for individuals' current and future wellbeing. The multi-dimensional poverty and health inequalities literature suggests that poor health and socio-economic conditions cluster in the general population, which may exacerbate societal inequalities over time. This study investigates how COVID-19-related health- and socio-economic vulnerabilities co-occur at the household level, and how they are distributed across household types and geographical areas in the United Kingdom. Using a nationally representative cross-sectional study of UK households and individuals and applying principal components analysis, we derived summary measures representing different dimensions of household vulnerabilities critical during the COVID-19 epidemic: health, employment, housing, financial and digital. Our analysis highlights four key findings. First, although COVID-19-related health risks are concentrated in retirement-age households, a substantial proportion of working-age households also face these risks. Second, different types of households exhibit different vulnerabilities, with working-age households more likely to face financial and housing precarities, and retirement-age households health and digital vulnerabilities. Third, there are area-level differences in the distribution of household-level vulnerabilities across England and the constituent countries of the United Kingdom. Fourth, in many households, different dimensions of vulnerabilities intersect; this is especially prevalent among working-age households. The findings imply that the short- and long-term consequences of the COVID-19 crisis are likely to significantly vary by household type. Policy measures that aim to mitigate the health and socio-economic consequences of the COVID-19 pandemic should consider how vulnerabilities cluster and interact with one another both within individuals and different household types, and how these may exacerbate already existing inequalities.